A Research Study on Molar Pragnencies, Treatment, Causes and its Effect on Human Body - Sumera Begum, Munazza Ayub, Sumaiya Zulfiqar, Tahira Fatima, Kashifa Ehsan, Naveed Fazal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Pregnancies in which eggs and sperm did not join correctly with a certain position and further growth does not occur, this will be known as Moral pregnancy. Methods: Moral pregnancy is considered as issue created in ovary of female where fertilization in a correct way does not occur and a times come when pregnancy ends and somehow, we called it as miscarriage. A study was held to check out the important highlights about moral pregnancies, its side effects and its outcomes. In this study, they measure the ratio of about 16,600 patients who was admitted. Here most of them was suffering with same symptoms in term of bleeding which determine that they have miscarriage. Results: About 93.2% patients was suffering with bleeding issues and severe pain. Different tests performed on them to know the exact reason of their issues. Either sperms were weak or egg of women was weak. Conclusion: Reason of occurrence of this type of fertilization. All of them was not coming for their regular checkup and was not taking proper treatment from gynecologists to solve their issues. Keywords: Moral pregnancy, sonography, high risk group, missed periods, bleeding.